Design of the Kua Chika Ecotourism Trail at the Amazon Center for Biodiversity and Tourism - González Villa, Angela Andrea
At present, the Center for Biodiversity and Tourism of the Amazon does not have an ideal environment for carrying out tourism and environmental practices, which is why the instructors of the two areas in question promoted the initiative of managing a project of a living classroom that strengthens the pedagogical actions of the different formations; In this first phase, the design of the Kua Chíka ecotourism trail was addressed, where relevant information was collected for its subsequent implementation. As a first action, a topographical survey of the area under study was carried out, which allowed knowing the terrain and making the layout of the selected route. After this, an inventory of fauna and flora of the wooded area was carried out, to identify the different species present in the area. The first two actions allowed the collection of necessary inputs for the planning of the interpretive scripting of the natural resources of the trail area. The information collected was analyzed and a map was designedand printed showing the route of the trail, the suggested places for the stations and the main points of interest. Finally, the map of the Kua Chica ecotourism trail located in the Center for Biodiversity and Tourism of the Amazon, intends to incorporate all the suitable components for its subsequent implementation